2013
DOI: 10.1039/c3dt51045j
|View full text |Cite
|
Sign up to set email alerts
|

A coumarin-based “turn-on” fluorescent sensor for the determination of Al3+: single crystal X-ray structure and cell staining properties

Abstract: An efficient Al(3+) receptor, 6-(2-hydroxybenzylideneamino)-2H-chromen-2-one (HBC), has been synthesized by condensing salicylaldehyde with 6-aminocoumarin. The molecular structure of HBC has been determined by a single crystal X-ray analysis. It was established that in the presence of Al(3+), HBC shows 25 fold enhancement of fluorescence intensity which might be attributed to the chelation-enhanced fluorescence (CHEF) process. HBC binds Al(NO3)3 in a 1 : 1 stoichiometry with a binding constant (K) of 7.9 × 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…The interaction of HL and Al 3+ [47][48][49]. Of course, all of these were further confirmed by ESI-MS, 1 HNMR titration.…”
Section: Uv-vis Analysissupporting
confidence: 52%
“…The interaction of HL and Al 3+ [47][48][49]. Of course, all of these were further confirmed by ESI-MS, 1 HNMR titration.…”
Section: Uv-vis Analysissupporting
confidence: 52%
“…In view of above we have planned to furthermore investigate the ability of PMP in detection of intracellular fluoride [31,[57][58][59][60][61]. For this study two types of cells viz.…”
Section: Preparation Of Cells and Detection Of F -By Receptormentioning
confidence: 99%
“…In general, as a hard-acid, it has been found that Al 3+ prefers a coordination sphere containing N and O as hard-base donor sites, on the other hand, the Schiff-base could provide a nitrogen-oxygen-rich coordination environment for the hard-acid Al 3+ [23][24][25][26]. Therefore, it can be conceived that the Schiff-base would develop a fluorescent probe for detection of Al 3+ .…”
Section: Introductionmentioning
confidence: 98%